2021
DOI: 10.3390/ijms22126528
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Stem Cell ‘Retirement Plans’: Growth, Regulation and Species Adaptations in the Retinal Ciliary Marginal Zone

Abstract: The vertebrate retina develops from a specified group of precursor cells that adopt distinct identities and generate lineages of either the neural retina, retinal pigmented epithelium, or ciliary body. In some species, including teleost fish and amphibians, proliferative cells with stem-cell-like properties capable of continuously supplying new retinal cells post-embryonically have been characterized and extensively studied. This region, termed the ciliary or circumferential marginal zone (CMZ), possibly repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 147 publications
(285 reference statements)
0
17
0
Order By: Relevance
“…In order to increase the neurogenic potential of the CMZ, attempts have been made to enhance the cell proliferation and differentiation in this zone using fish and amphibian models. This can be exemplified by the ability of CMZ cells to maintain a high level of proliferative activity, as has been reported for dmbx1a germline zebrafish mutants [ 69 ]. It has also been shown that the activation of the IGF receptor gene ( Igf1r ) in medaka causes a decrease in the cell cycle length and an increase in the production of differentiated neurons [ 70 ].…”
Section: Intrinsic Retinal Regeneration Cell Sources and Their Implic...mentioning
confidence: 87%
“…In order to increase the neurogenic potential of the CMZ, attempts have been made to enhance the cell proliferation and differentiation in this zone using fish and amphibian models. This can be exemplified by the ability of CMZ cells to maintain a high level of proliferative activity, as has been reported for dmbx1a germline zebrafish mutants [ 69 ]. It has also been shown that the activation of the IGF receptor gene ( Igf1r ) in medaka causes a decrease in the cell cycle length and an increase in the production of differentiated neurons [ 70 ].…”
Section: Intrinsic Retinal Regeneration Cell Sources and Their Implic...mentioning
confidence: 87%
“…The mammalian ciliary body (CB), located between ora serrata of the neural retina (NR) and the iris, has an anatomical homology with the ciliary marginal zone (CMZ) of fish and amphibians, an undifferentiated region known as a source of new neurons and glial cells of the retina in development and regeneration (reviews: [ 28 , 87 , 88 ]). However, Miles and Tropepe [ 88 ] insist not to confuse the CB region with the ciliary, non-stratified region of the retina, which contains low-differentiated cells in vertebrates.…”
Section: Cell-type Conversion Of Ciliary Body Epithelial Cellsmentioning
confidence: 99%
“…In general, the data obtained in vitro are the evidence of the initially laid down broad competence of RPE cells in adult mammals and humans, manifested in vitro along the initial epithelial, neural, and mesoderm-associated pathways of differentiation. Taking into account this behavior of mammalian and human RPE cells during in vitro cultivation, some authors [ 88 , 203 , 204 ] regard RPE (or a certain population of its cells) as stem cells (RPESCs), a priori assuming their presence in human RPE. However, despite the discovered cellular heterogeneity in RPE [ 205 , 206 ], there is no direct evidence of the presence of RPESCs in it.…”
Section: Cell-type Conversion Of the Retinal Pigment Epithelial (Rpe)...mentioning
confidence: 99%
“…For example, in catshark telencephalic neurogenic niches, different subtypes of progenitor cells like radial glial progenitor cells, intermediate progenitor-like cells and migrating neuroblasts have been described based on the expression of typical (and evolutionary conserved) markers of each of these progenitor cell types (Docampo-Seara et al, 2020). Some of the best characterized neurogenic niches in the CNS of fish are also found in the retina (reviewed in Amato et al, 2004;Moshiri et al, 2004;Ail and Perron, 2017;Miles and Tropepe, 2021) and, again, work in teleost models has provided important information on the genes and molecular pathways controlling postnatal neurogenesis from progenitor cells in these niches (e. g., Conner et al, 2014). In catsharks, as in teleost and other fish usually used as models to study retinal neurogenesis, the peripheral postnatal retina contains a circumferential ring of proliferating cells located between the ciliary epithelium and the mature central retina known as ciliary marginal zone (CMZ) (Sánchez-Farías andCandal 2015, 2016;Ferreiro-Galve et al, 2021;Hernández-Núñez et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%